GENDER JUSTICE IN THE SHARING OF INHERITANCE AND IMPLEMENTATION IN INDONESIA - Hisam Ahyani; Haris Maiza Putra; Muharir Muharir; Encep Taufik Rahman; Mustofa Mustofa (Asy-Syari'ah, 2022)
Fairness in inheritance distribution between men and women in Indonesia is still an exciting topic to discuss. It is proven that classical Islamic thought says that men's and women's portions in inheritance distribution are final, as stated in the Qur'an Surat an-Nisa verse 11. However, contemporary Islamic thought sees it as a rule that needs to be contextualized to current situations. This progressive thinking about inheritance distribution was pioneered by gender activists who saw that Fiqh Mawaris has a gender bias and discrimination. Therefore, the application of the "gender-friendly justice" concept in the inheritance distribution in Indonesia needs to be put forward. This research analyses the "gender-friendly justice" concept in inheritance law and its application in Indonesia. This study uses Sigmund Freud's gender theory, with an analytic descriptive method focusing on the problem of inheritance distribution in Indonesia. The research results prove that the concept of "gender-friendly justice" in the inheritance distribution refers to the agreement principle and the gender equity principle, where the application is carried out based on the fairness principle. The gender equality principle is implemented by prioritizing the concept of rahmatan lil'alamin, namely equality as servants and caliph of Allah, equality in receiving primordial agreements and cosmic drama events, and reaching achievements.